Effects of auxin doses onrooting of Juniperus L. - Tektas, Ibrahim; Türkoğlu, Nalan; Cavusoğlu, Seyda (Progress in Nutrition, 2017)
The present study was conducted to investigate the rooting ratios of cuttings taken from naturally grown Greek juniper trees of Gevaş and Çatak (Van) regions at different dates in 2013 and 2014 and under different hormone doses. The cuttings taken in October and December of 2013 and April of 2014 were immersed into water for 24 hours, then they were dipped into 3000 ppm, 5000 ppm and 7000 ppm NAA and IBA hormone solutions for 5 seconds. Cuttings were planted into growth mediums for rooting. For reliable rooting, the most proper hormone concentration was identified as 5000 ppm NAA and the most proper planting time was identified as April.